Factors Affecting Economic Wellbeing of the Cooperatives Members in Rupandehi District - Gaire, Laxman Prasad (Journal of Rapti Babai Campus, 2025)
This quantitative study seeks to evaluate the factors affecting economic well-being of cooperative members. The 407 survey data for the study was gathered from the cooperative members of Rupadnehi district. The likert scale data consisted from primary sources. The central tendency of the variables were also investigated using descriptive analysis that suggested all independent variables contributed to the creation of economic well-being of cooperative members. To determine the correlation between the variables, the Pearson correlation was used. The result indicated that there is a significant and positive relationship between all variables. It indicates that the members' participation, credit facilities, training and financial inclusion, and economic well-being are associated. There is also a significant and positive correlation between independent variables each other. The effect of factors on the economic well-being of cooperative members was analyzed by using multiple linear regression models. Further, the result shows that members' participation, credit facilities, training, and financial inclusion have a positive and statistically significant impact on economic well-being. Therefore, the study reveals that the economic well-being of cooperatives is affected by independent variables. It helps policymakers, cooperative organizations, and further research for new insights to improve the study on the economic well-being of cooperative members.